2013
DOI: 10.4028/www.scientific.net/amr.687.45
|View full text |Cite
|
Sign up to set email alerts
|

Report from 13<sup>th</sup> ICPIC and 7<sup>th</sup> ASPIC: New Trends on Concrete-Polymer Composites

Abstract: The field of polymers in concrete is consolidated in the construction industry. The future of polymers in concrete is governed by the synergic interaction between these materials, in order to contribute significantly towards a more sustainable construction. Concrete-polymer composites (C-PC) have excellent mechanical and durability properties. Appropriate combination of polymers and classical construction materials provides opportunities for innovative applications and systems. This paper highlights the innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…8 and 9. The modified cement mortar with PVA has improvement in structural and adjustments so that is depended on process of hydration, FTIR of spectra analysis have proved through form new band due to PVA affects under dry curing condition, and form film prevents loss moisture from cement mortar (Aguiar et al, 2013). Through that used XRD systems to determine active reactions energy and observer chemical change of PVA in modified cement mortar demonstrated that after PVA can be added mixture of sample, the polymer delays the hydration because the gel formed and prevents loss water, as shown in…”
Section: Direct Tensile Strengthmentioning
confidence: 99%
“…8 and 9. The modified cement mortar with PVA has improvement in structural and adjustments so that is depended on process of hydration, FTIR of spectra analysis have proved through form new band due to PVA affects under dry curing condition, and form film prevents loss moisture from cement mortar (Aguiar et al, 2013). Through that used XRD systems to determine active reactions energy and observer chemical change of PVA in modified cement mortar demonstrated that after PVA can be added mixture of sample, the polymer delays the hydration because the gel formed and prevents loss water, as shown in…”
Section: Direct Tensile Strengthmentioning
confidence: 99%
“…We would like to follow the idea which has been already presented [1] in Istanbul during the 7 th ASPIC. It is our intention that the paper would be continuation of the discussion on further C-PC development trends which started in Istanbul [2].…”
Section: Introductionmentioning
confidence: 99%